Romania : Third Review Under the Stand-By Arrangement-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Romania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper discusses key findings of the Third Review of Romania's economic performance under a program supported by a 24-month Stand-By Arrangement (SBA). The authorities are on track to achieve their 2011-12 deficit targets, but stepped-up efforts are needed on key structural reforms. Inflation has dropped sharply, reflecting food prices deflation and the removal of the VAT base effect. All end-September quantitative performance criteria and indicative targets were met, and inflation returned to the inner band of the inflation consultation mechanism.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet